205k views
1 vote
Explain how to solve this system algebraically

Explain how to solve this system algebraically-example-1
User Theprole
by
5.3k points

2 Answers

3 votes
4x-2y=-12.....I
2x-y=-6.......II

2x+6=y......iii

From eqn I
4x-2(2x-y)=-12
or,4x-4x+2y=-12
or,2y=-12
Y=-6

In eqn iii
2x+6=-6(y=-6)
or,2x=-12
X=-6
User Wesley Chang
by
5.1k points
4 votes

Answer:

take the -12 to behind the equal and replace with 0 then solve the polynomial

User Izion
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.